Temporal and Spatial Distribution of Dengue Vector Mosquitoes and their Habitat Patterns in Penang Island, Malaysia - Rahman G. M., Saifur; Ahmad, Abu Hassan; Dieng, Hamady; Md Rawi, Che Salmah; Ahmad Ramli, Saad; Satho, Tomomitsu (Bio Online Journals, 2013)
We studied the diversity of Aedes breeding sites in various urban, suburban, and rural areas over time between February 2009 and February 2010 in the dengue endemic areas of Penang Island, Malaysia. We categorized the breeding sites and efficiency, and identified the key breeding containers. Among the 3 areas, the rural areas produced the highest container index (55), followed by suburban (42) and urban (32) areas. The numbers of key premises and containers were significantly higher (P < 0.000) in rural areas. The class 1 containers were identified as the key containers with higher productivity and efficiency, although class 2 and class 4 are the highest in numbers. Aedes aegypti immatures were found mostly in drums, water reservoirs, and polyethylene sheets, while mixed breeding was more common in buckets and empty paint cans in urban and suburban areas. Aedes albopictus was found mainly in miscellaneous containers such as drums, empty paint cans, and covers in all areas. The main potential containers indoors were drums, water reservoirs, and empty paint cans, and containers outdoors included empty paint cans, drums, and polyethylene sheets.